Chinese energy and fuels research priorities and trend: A bibliometric analysis. (May 2016) - Chen, Hua-Qi; Wang, Xiuping; He, Li; Chen, Ping; Wan, Yuehua; Yang, Lingyun; Jiang, Shuian
Abstract: This study aims to summarize an overview of Chinese energy and fuels research using comprehensive bibliometric analysis measures based on data extracted from the Science Citation Index Expanded database from 1993 to 2012. Keyword analysis was used to assess and evaluate the priorities, topics and topic shifts using the Thomson Data Analyzer (TDA). In particular, popular topics were demonstrated using bubble charts. The results show that solid oxide fuel cell (SOFC), lithium-ion batteries and hydrogen were the most important topics. The priorities of energy and fuels research in China were hydrogen and fuel cells, lithium-ion batteries, biodiesel and biomass, coal, and solar energy, respectively. Of course, lithium-ion batteries have entered substantive application stages in China in 2012. The hydrogen economy has been formed. Biomass and biodiesel research was the popular topic, as well as hydrogen and fuel cells, lithium-ion batteries. But solar energy was not still "hot". The characteristics of the types of documents, languages, year, journals, institutions and co-publishing countries were analyzed, as well as the keyword occurrence frequencies. It can be stated that 19, 089 articles by Chinese authors were published in 106 journals. More than one-third of the articles were published in the Journal of Power Sources, the International Journal of Hydrogen Energy and Bioresource Technology . The Chinese Academy of Science, Tsinghua University, China University of Petroleum, Shanghai Jiao Tong University, and Zhejiang University were the top five institutions. The USA was the leading inter-collaborative country, followed by Japan, the UK and Canada. The findings presented here provide an overall picture of the development of Chinese energy and fuels research and could also help policy makers assess the impact of the resource allocation decisions made in the past to develop energy policies and strategies for the future.